2019
DOI: 10.1002/mrm.27887
|View full text |Cite
|
Sign up to set email alerts
|

Rhein‐based necrosis‐avid MRI contrast agents for early evaluation of tumor response to microwave ablation therapy

Abstract: Purpose Early evaluation of tumor response to thermal ablation therapy can help identify untreated tumor cells and then perform repeated treatment as soon as possible. The purpose of this work was to explore the potential of rhein‐based necrosis‐avid contrast agents (NACAs) for early evaluation of tumor response to microwave ablation (MWA). Methods 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyl tetrazolium bromide (MTT) assay was performed to test the cytotoxicity of rhein‐based NACAs against HepG2 cells. Rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It was demonstrated that GdL 2 could enhance the ablated lesion in rats with liver MWA as early as 2 h post ablation and could maintain a stable contrast ratio of ablated lesion to normal liver until 24 h post ablation, which supported its potential use for early assessment of thermal ablation therapy response [48]. Then the capability of GdL 2 to distinguish residual tumor from MWA lesion was evaluated in a rat model of liver tumor hyperintensity relative to normal liver at 3 h post injection (Figure 4B), thus allowing noninvasive identification of unaffected residual tumor [48]. Moreover, it was found that the optimal time window for visualizing the MWA lesion appeared at 2.5 to 3.5 h post injection of GdL 2 in rat models of liver tumor MWA [48].…”
Section: Early Monitoring Of Tumor Response To Therapymentioning
confidence: 86%
See 4 more Smart Citations
“…It was demonstrated that GdL 2 could enhance the ablated lesion in rats with liver MWA as early as 2 h post ablation and could maintain a stable contrast ratio of ablated lesion to normal liver until 24 h post ablation, which supported its potential use for early assessment of thermal ablation therapy response [48]. Then the capability of GdL 2 to distinguish residual tumor from MWA lesion was evaluated in a rat model of liver tumor hyperintensity relative to normal liver at 3 h post injection (Figure 4B), thus allowing noninvasive identification of unaffected residual tumor [48]. Moreover, it was found that the optimal time window for visualizing the MWA lesion appeared at 2.5 to 3.5 h post injection of GdL 2 in rat models of liver tumor MWA [48].…”
Section: Early Monitoring Of Tumor Response To Therapymentioning
confidence: 86%
“…Therefore, GdL 1 may serve as a potential MRI contrast agent for early evaluation of tumor response to necrosis-inducing therapies. [48]. The results demonstrated that GdL 3 was not as safe as GdL 1 and GdL 2 in the concentration range from 25 to 1000 μM [48].…”
Section: Early Monitoring Of Tumor Response To Therapymentioning
confidence: 88%
See 3 more Smart Citations